(untitled) (Journal of Health Sciences, 2013)
Introduction: Defensins are small anti-microbial peptides produced by epithelial cells. These peptides have a broad range of actions against microorganisms, including Gram-positive and Gram-negative bacteria.Human defensins are classifi ed into two subfamilies, the α-, and β- defensins, which differ in their distribution of disulphide bonds between the six conserved cysteine residues. Defensins are found in salivaand others compartments of the body. Human β defensins 2 (hBD2), beta defensins 4 (hBD4) and alpha defensins 4 (hNP4) in saliva may contributes to vulnerability or resistance to caries. This study aimed to determine a possible correlation between caries and levels of defensins measuring the expression in gingival tissue and concentrations in saliva samples.Methods: Oral examinations were performed on 100 adults of both genders (18-30 years old), and unstimulated whole saliva was collected for immunoassays of the three peptides and for the salivary pH, buffercapacity, protein, and peroxidase activity. mRNA levels of defensins in gingival sample were assessed by semi-quantitative RT-PCR technique.Results: The median salivary levels of hBD2 and hBD4 were 1.88 μg/ml and 0.86 μg/ml respectively for the caries-free group (n=44) and 7.26 μ/ml (hBD2) and 4.25 μg/ml (hBD4) for all subjects with evidenceof caries (n=56). There was no difference in the levels of hNP4, salivary pH, and proteins between groups, however the peroxidase activity and buffer capacity (interval 6.0-5.0) were reduced in caries group. Transcriptional levels of hBD2 and hBD4 did correlate with caries experience, the mRNA expression of hBD2 and hBD4 were signifi cantly higher in patients with caries than in patients with no-caries (p < 0.01).Conclusion: We conclude that high salivary levels and expression of beta defensins, low peroxidase activity and buffer capacity may represent a biological response of oral tissue to caries. Our observation couldlead to new ways to prevent caries and a new tool for caries risk assessment.